Contingent Valuation Method: Valuing Cultural Heritage - Chiam Chooi Chiam; A.R. Khalid; Y. Rusli; R. Alias (2011)
Cultural heritage is not easy to be valued in a market because it is a very unique product which gives a community (ies), nation(s) an identity and a sense of belonging. Debate on the valuation of cultural heritage surrounds despite growing attention by economists and policy makers. The attention on the estimation of economic values for cultural goods and services has been great by economics throughout the past two decades (Choi, et al., 2009; Kaminski, McLoughlin, & Sodagar, 2007; Navrud & Ready, 2002, Noonan, 2003; Venkatachalam, 2004). The two stated preference methods which are commonly used in valuing non-use goods; i.e. contingent valuation method and choice modelling. Each of these two valuation method has its own strengths and weaknesses and may even complement each other depending on the parameters of the study. However, according to Kaminski et al., 2007; Noonan, 2003, the usage of choice modelling to estimate cultural values has been limited due to the growing usage of contingent valuation. Therefore, this paper will discuss contingent valuation method in valuing amenities and aim to contribute the knowledge on contingent valuation method for nonmarket goods. (Abstract by author)